Body dysmorphic disorder and orthodontics - an overview for clinicians - Anthony Marshneil Trista; Farella Mauro (Sciendo, 2014)
Introduction: Patients with body dysmorphic disorder (BDD) often seek aesthetic medical treatment including orthodontics to correct their perceived physical defects. When the disorder pertains to the dentofacial region, it is important for orthodontists to be familiar with this condition.